Kajian Teknik Dan Nilai Ekonomi Pengolahan Batu Kapur Pada Pertambangan Batu Kapur Rakyat Bukit Tui, Padang Panjang, Sumatera Barat - Randa Septian Putra; Rusli HAR (Journals Mining Engineering : Bina Tambang, 2020)
Abstract.The people’s limestone mining in Bukit Tui has a mineable reserve of 12,826,641.60 MT. This study analyzes the limestone processing techniques in the Bukit Tui people's limestone mining and also analyzes the economic feasibility of the processing using the Discounted Cash Flow method. The efficiency of the limestone furnace at the Bukit Tui processing plant is very low, at 26.63% for each ton of lime produced with fuel consumption of 336.18 kg/ton of lime which generated. This is due to the incomplete combustion process. To increase the combustion efficiency, a furnace modification is needed, in the form of adding fans and recuperators. In the case of Bukit Tui limestone processing, the air needed is 8,928.42 kg. Therefore to complete the combustion process, a fan is needed to supply air to the furnace with a discharge of 0.07 m3/s. And if combustion takes place completely, fuel consumption will be reduced to 89.49 kg / ton of lime produced. Based on an analysis of economic value, it can be seen that the economic value of the Bukit Tui limestone processing can be declared economically feasible. However, it still needs to be adjusted to the processing technique to match the good mining practice rules (GMP).Keywords: Limestone, GMP, Processing Techniques, Furnace Efficiency, Economic Value